Rabindranath Tagore's literary representation of Muslims - Quayum, Mohammad Abdul (2016)
Rabindranath Tagore, the iconic Asian writer, has of late been accused of Hindu chauvinism by some of his critics. Was he a bigoted writer? Was he anti-Muslim? Did he seek to establish a Hindu Raj in the subcontinent by depriving and disenfranchising the Muslims? Or was he in favour of Hindu-Muslim unity in order for creating a peaceful, prosperous and progressive India? Was his cosmopolitanism inclusive of all ethnic and religious groups, or was it besmirched by his antipathy towards Muslims? These are some of the issues that will be addressed in this paper through an analysis of his letters, speeches, essays, poetry and fiction.